The Effect of Parental Social Support on Self Esteem in Tarokan 3 Elementary School Children, Kediri Regency - Karisna Fitriawati (Jurnal Scientia, 2022)
Learning is not only obtained within the scope of the school, the most important learning is obtained from parents or family. Parents play an important role in providing learning to children, especially for personality formation. The formation of personality in children can be done through social support from parents.The purpose of this study is to (1) prove the effect of social emotional support of parents on the Self Esteem of children at the Tarokan 3 State Elementary School, Kediri Regency. (2) Proving the effect of parental appreciation of social support on Self Esteem of children at Tarokan 3 State Elementary School, Kediri Regency. (3) Proving the effect of parental information social support on Self Esteem of children at Tarokan 3 State Elementary School, Kediri Regency.